Pengaruh Kombinasi Model Pembelajaran Kooperatif dan Pengetahuan Dasar Matematika Terhadap Hasil Belajar Matematika Siswa Kelas X SMA Negeri 2 Kendari - Muhammad Sudia; Faad Maonde; Mahdaniah Hasan (Jurnal Pendidikan Matematika, 2016)
The experimental design used in this research was factorial 2x2 design. The purpose of this research was to study about the effect of combination between cooperative learning model called Jigsaw-TSTS, STAD and mathematics as a level that is a basic knowledge of mathematics above average and below average towards students’ learning outcomes of Class X SMAN 2 Kendari. The sample of this research was 40 students. The result of this research showed that the combination interaction factor of cooperative learning model and mathematics through design A*B, A A*B, B A*B, and A B A*B (A = A combination of cooperative learning model and B = A mathematics) using F-test, was accepted (H0) which means all four models that had been decided have no significant effect. Therefore the mean of learning outcomes in all of the cells formed by the factors A and B had small differences.